Peranan Pencak Silat sebagai Wahana Moderasi Beragama di Cabang Langkat - Hakim, Muhammad Zulfri (YASIN, 2024)
This research aims to determine the role of Pencak Silat as a vehicle for religious moderation in the Langkat branch. This research is field research (Fiel Research) with a qualitative approach, data collection techniques are processed from the results of direct observation by looking at Tapak Suci training activities, field interviews, and documentation, data analysis is carried out using descriptive analysis which includes: data collection, data filtering, data classification and drawing conclusions. The results of this research show that the Tapak Suci pencak silat organization was built by suppressing the religious egoism carried by each of its members, as referred to in functional improvement, this is referred to as Adaptation. Then, tolerance is maintained in order to balance the situation of the organization itself using rules or norms that have been established and understood by all its members.